Meningkatkan Produksi UMKM melalui Pelatihan Produksi dan Pemasaran Briket Arang - Muttaqien Dawood; Maisyuri Maisyuri; Salawati Salawati; Aftri Shanda; Muhammad Akram (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2023)
The aim of executing this communal activity is to enhance comprehension of the significance of utilizing coconut shell charcoal briquettes as a substitute for fuel in culinary pursuits, especially when grilling food. In addition, the training for making coconut shell charcoal briquettes for the residents of Gampong Kuta Krueng consisted of three stages, namely: the Preparation Stage, the Training Stage, and the Evaluation Stage.  The purpose of this initiative was to offer instruction to the inhabitants of Gampong Kuta Krueng on producing coconut shell charcoal briquettes as a substitute energy source, particularly for cooking purposes. It is anticipated that this endeavor will proceed effortlessly and the community's awareness will be heightened, along with government backing, leading to expansion in both manufacturing and trade.